种基于双腔体式集热器的高效塔式太阳能热发电系统及方法 (2018)
本发明属于太阳能光热发电技术领域，具体涉及种基于双腔体式集热器的高效塔式太阳能热发电系统。现有的塔式太阳能热发电系统的热效率较低。本发明包括集热塔，其特点是：还包括近太阳定日镜场，远太阳定日镜场，安装在集热塔顶部的汽水分离器，以及安装在集热塔上的上腔体式集热器和下腔体式集热器；近太阳定日镜场、集热塔和远太阳定日镜场在水平方向上依次排列；上腔体式集热器的入口与给水管道连通，上腔体式集热器的出口连接到汽水分离器的入口；汽水分离器的饱和蒸汽出口连接到下腔体式集热器的入口，该汽水分离器的饱和水出口连接到给水管道上，下腔体式集热器的出口与过热蒸汽管道连通。本发明系统热效率高，提高系统聚焦的准确度。 The invention belongs to the technical field of solar photothermal power generation, and in particular, relates to an efficient tower solar thermal power generation system based on a double-cavity heat collector. A traditional tower solar thermal power generation system is lower in heat efficiency. The efficient tower solar thermal power generation system based on the double-cavity heat collector comprises a heat collecting tower, and is characterized by further comprising a near solar heliostat field, a far solar heliostat field, a steam-water separator mounted at the top of the heat collecting tower, and an upper-cavity heat collector and a lower-cavity heat collector mounted on the heat collecting tower; the near